Designing and building fuel cells - Spiegel, Colleen (McGraw-Hill, 2007)
Authoritative and practical, Designing and Building Fuel Cells features: Complete information on stack design, the latest fuel cell modeling techniques, guidance on cutting-edge materials and components, expert accounts of fuel cell types, processing, and optimization, a step-by-step example for constructing a fuel cell.